If You Teach Them To Write They Will Read - Meadows, Feland L.; C., Roberto (European Scientific Journal, ESJ, 2016)
There is a reading crisis in the U.S. where many teachers do not know how to teach children to read. â€œYou learn to read from kinder to 3rd grade, so that you can read to learn from 4th grade on.â€ Unfortunately sixty five percent (65%) of all US fourth graders cannot read at grade level. (The Annie E. Casey Foundation: National KIDS COUNT. 2015). Research makes it clear that most children require direct instruction in order to learn to read. (â€œNational Reading Panelâ€ Chapters 2 & 3. 2000) Over a period of 40 years, the writer has prepared more than 2,500 Montessori Teachers in Canada, U.S.A., Mexico, Costa Rica, Panama, Ecuador, Brazil, France and Switzerland. His alumni have opened 25 Montessori schools in Costa Rica and more than 100 Montessori schools in Mexico. The author and his alumni have used the teaching strategies described in this monograph to teach thousands of children to write and read successfully. This study also challenges the Conventional Wisdom that â€œbooks are in print so we must teach children to print.â€ The writerâ€™s research demonstrates that Conventional Wisdom is wrong and he challenges the reader to consider the benefits of teaching children to master longhand cursive writing instead of print, because it facilitates both the process and the quality of writing and reading.